Pengaruh Online Customer Review Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Melalui Kepercayaan Pelanggan: Studi Kasus Produk Fashion Pada Platform Shopee Di Teluk Pucung Kota Bekasi - Alysha Lathifah; Hadita Hadita; Neng Siti Komariah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the effect of online customer reviews and electronic word of mouth on purchase decisions through customer trust. The research method used in this research is quantitative method. Respondents in this study were consumers using Shopee in Teluk Pucung, Bekasi City. The population in this study are customers who have purchased fashion products online on the Shopee platform. This sampling technique uses the Accidental sampling method which are calculated using the Hair formula. Based on calculations using the Hair formula, it can be concluded that the number of samples obtained was 180 samples. The data used in this study is primary data, namely by distributing questionnaires. The measurement scale used is a Likert scale. The data analysis technique used in this research is structural equation modeling or SEM with the help of SmartPLS 4.0 software. The results showed that the online customer review variables had a positive and significant effect on customer trust, the electronic word of mouth variables had a positive and significant effect on customer trust, the customer trust variables had a positive and significant effect on purchase decisions, the online customer review variables had a positive and significant effect on purchases decisions through customer trust, and electronic word of mouth variables had a positive and significant effect on purchase decisions through customer trust.